Media Massa dan Globalisasi Produk Simbolik - Narendra, Pitra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2000)
The mode of production and consumPtion of the advanced capitalism are marked by the presence of the symbolic product. The advent of the symbolic product cannot dissociated from the changing human consciousness about the time and space. The human importance to subject time and space had invented the communication revolution and the flexible accumulation of capital. These two elements influence the emergence of the symbolic product and disseminating it throughout the globe.